The Swedish property crisis in retrospect: a new look at appraisal bias - Enstroem, Rickard (My University, 2005)
In the early 1990s, Sweden suffered from a severe property crisis. This study aims to analyze the market for income properties in Sweden over a 20‐year period, 1980‐2000, taking a fresh look at describing the depth of the property crisis. The study specifically attempts to examine if appraisal bias was present when the state‐owned Nordbanken bank foreclosed on a large number of properties.
Keywords: real estate; property; prices; Sweden